Interlocução cultural Brasil e Estados Unidos durante a 2ª guerra mundial: uma análise enunciativa multimodal a partir da linguagem de Zé Carioca e Pato Donald em cinema de animação. - Malhoit, Monika Lira (2018)
The present work is justified as it analyses a cinematographic production entitled “Saludos Amigos” authored by Walt Disney, created and experienced within a period of great ideological conflicts during World War II. The production of the film was in response to a request by then-President Franklin Delano Roosevelt, whose intention was to join north and south american forces against Adolf Hitler's nazi Germany's dictatorial regime. Thus, this research had as its’ main objective to investigate the cultural relationship between Brazil and the United States in the multimodal language of the characters Pato Donald and Zé Carioca in the film “Saludos Amigos” screened in theaters in 1942. This study focuses on the Multimodal Enunciative approach presented in the language of the characters leveraging Émile Benveniste's Theory of Enunciation (2005, 2006) as well as the classification within the Gesture / Speech matrix of gestures proposed by David McNeill (1985, 1992). Accordingly, Semantic and Semiotic aspects were studied which allowed for reading implicit meaning present in character language. The study pointed to the field of the three deic elements: Ego, Hic, Nunc - which in Latin mean - I, Here, Now - which indicate - people, time and space in the vast breadth of linguistic content of the mediation instance between language and character speech, the narrator, and the scene of the film. This was a documentary-type qualitative research with a new look taken at “Saludos Amigos”, and while the film highlights four countries of Latin America, this study only focused on the Brazilian scenario. The methodological procedures were based on character discourse, using the entire film’s audiovisual transcription, selection and analysis of the enunciative scenes between the characters Donald Duck and Zé Carioca that contemplated the indicative elements of language, henceforth called “deictic", as well as gestures and speech, presented here as two inseparable facets belonging to the same matrix of linguisticcognitive functioning. Data found showed that Donald and Zé Carioca are marked in language and through language as representatives of their countries, either in their speech identity traces (language), or in the semiotic traces shown by their bodies. The film maker’s selection of animal characters, according to their natural characteristics of duck "defender" and parrot “joker”, in our opinion had a direct relationship with the "Good Neighbor Policy" which it was intended to achieve. The relationship which was built as a weapon of war continues today given the influence that the American Way of Life and capitalist model continue to exert in Brazilian society. Therefore the aim of this study is to contribute to the Benveniste's theoretical axioms which may lead to new dialogues amongst related fields of scientific knowledge using the same approach.